Workstation Design Enterprise / Lorita Gadol ... [et al.] - Gadol, Lorita; Ismail, Nur Hidayah; Gambud, Hailin; Husin, Mohd Hanis; Zamzuri, Shaliza; Abdul Ghani, Kalthom (Faculty of Information Management, 2002)
Our business name is WORKSTATION DESIGN ENTERPRISE that offers services in designing and printing T-shirt and banner. This business will be operated on 19th September 2002. Since there are higher demands, we take this opportunity to satisfy customers' want. Our main targets are students, and organizations. We are trying to be quality oriented. We hire experience designer and printer in order to attract people since we are newcomer in this business and compete with other competitors. In the other hand the location that we choose is one of the people converge. Hopefully that this will be one advantage for us in getting more order and opportunity.